2020
DOI: 10.21776/ub.mnj.2020.006.02.1
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Manifestation on Hospitalized Patient With Probable Covid-19 in Saiful Anwar Hospital Indonesia (Serial Cases)

Abstract: Background: Coronavirus disease 2019 (Covid-19) caused by SARS-Cov-2 had been spreading worldwide including Indonesia, but In Indonesia, it was difficult to diagnose confirmation Covid-19 by Polymerase Change Reaction (PCR). and in clinical practice to treat covid-19, Indonesia Health Ministry use term probable covid-19 for patients under observation Covid-19, but study for neurological manifestation on probable Covid-19 is very lacking. Objective: Knowing the neurological manifestation of patient probable Cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This ratio was also higher in males who were had acute ischemic CVA. 13,17,22,[25][26][27][28][29][30] Regarding the mean age of the patients suffering from acute ischemic CVA, with a COVID-19 infection, almost all of the included reports showed a mean age of at least 60 years old. Only two studies reported a lower mean of age, 14,23 and one of them had only included patients below 50 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…This ratio was also higher in males who were had acute ischemic CVA. 13,17,22,[25][26][27][28][29][30] Regarding the mean age of the patients suffering from acute ischemic CVA, with a COVID-19 infection, almost all of the included reports showed a mean age of at least 60 years old. Only two studies reported a lower mean of age, 14,23 and one of them had only included patients below 50 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Autopsy reports of deceased COVID-19 patients revealed brain tissue oedema and partial neuronal degeneration [23]. Badrul et al, from Indonesia, reported neurological manifestations in 3-4% out of 114 COVID-19-infected patients; thrombotic stroke was the most common followed by myeloid tumours and hypoxic-ischemic encephalopathy (HIE) [41]. Farzad et al reported a series of six patients younger than 55 years of age affected with COVID-19 and diagnosed with stroke.…”
Section: Neurological Manifestations Of Sars-cov-2mentioning
confidence: 99%
“…In Indonesia, the number of tuberculosis cases found and treated in 2020 was 344,992, with 11% being extrapulmonary tuberculosis (6). Emerging at the end of 2019, COVID-19 has infected 60 million people and caused 1.5 million deaths worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…An exaggerated inflammatory response causes damage to these organs. Although most symptoms are in the respiratory sys-tem, neurological manifestations are often found, proving that COVID-19 may act as an opportunistic pathogen in the nervous system, especially the brain (6,8,9). Several neurological manifestations were found, including stroke, polyneuropathy, myopathy, and seizures, but there are still limited data about COVID-19 in tuberculous meningoencephalitis (4,9).…”
Section: Introductionmentioning
confidence: 99%